How to say no and keep your friends : peer pressure reversal for teens and preteens - Scott, Sharon (Amherst, Mass. : Human Resource Development Press, 1997)
Provides advice for developing a personal set of values and how to cope with peer pressure.
Young Adult
Young Adult
Keywords: Adolescent psychology; Social interaction; Peer pressure in adolescence; Adolescent psychology; Interpersonal relations; Peer pressure